Moodle y su Aporte en el Aprendizaje de la Asignatura de Lengua y Literatura en los Estudiantes de Educación Básica Superior, de la Unidad Educativa Aurora Estrada y Ayala de Ramírez Pérez, Periodo Académico octubre 2024 - marzo 2025 - Cevallos Cruz, Frycson Steveen (2025)
The present study aims to determine the contribution of Moodle in the learning of the subject of Language and Literature in the students of higher basic education of the Educational Unit Aurora Estrada y Ayala de Ramirez Perez, during the academic period October 2024 - March 2025. It is based on the problem of the digital gap and the lack of innovative didactic strategies that affect academic performance in this subject. The methodology used was of mixed approach, with a descriptive and analytical design. Surveys and observations were applied to collect data on the use of Moodle in the classroom. The results show that the platform facilitates the personalization of learning, promotes student autonomy and improves interaction in collaborative activities. However, difficulties were identified in technological adaptation and in the long-term evaluation of the impact on academic performance. It is concluded that Moodle is an effective tool to enhance Language and Literature learning, allowing teachers to optimize their pedagogical strategies and offering students a more dynamic and accessible learning experience. It is recommended to strengthen teacher training in the use of this platform and to extend the implementation time in order to evaluate its long-term impact.